The application of andragogy principles in the learning process for the package C equality program at PKBM Amanah Ummat, Batua Village, Manggala District, Makassar City - Djamaluddin, Rizky Yuliyanti (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2023)
This study aims to examine the application of andragogy principles to the learning process of the package C equivalency program at PKBM Amanah Ummat, Batua Village, Manggala District, Makassar City. This study uses a qualitative research approach with a case study type of research. The subjects of this study were the Package C tutors and the Chairperson of PKBM Amanah Ummat, Batua Village, Manggala District, Makassar City. Data collection was carried out using Interview, Observation and Documentation Methods. The techniques used in data analysis are data reduction, data presentation, and drawing conclusions. The triangulation used to explain the validity of the data is method triangulation. The results of the study show that the 5 principles that the researcher chose have all been implemented by the tutor. However, for every principle chosen, not all tutors implement it. As with the principle of readiness, based on the results of interviews conducted by researchers, information was found that there was only 1 tutor who applied this principle. Apart from that, information can be found on the principle of participation that there is only 1 tutor who actually applies this principle.